An Improved Mathematical Model for Computing Power Output of Solar Photovoltaic Modules - Abdul Qayoom, Jakhrani; Saleem, Raza Samo; Shakeel Ahmed, Kamboh; Jane, Labadin; Andrew Ragai, Henry Rigit (Hindawi, 2014)
It is difficult to determine the input parameters values for equivalent circuit models of photovoltaic modules through analytical methods.Thus, the previous researchers preferred to use numerical methods. Since, the numerical methods are time consuming and need long term time series data which is not available in most developing countries, an improved mathematical model was formulated by combination of analytical and numerical methods to overcome the limitations of existing methods. The values of required model input parameters were computed analytically. The expression for output current of photovoltaic module was determined explicitly by Lambert W function and voltage was determined numerically by Newton-Raphson method. Moreover, the algebraic equations were derived for the shape factor which involves the ideality factor and the series resistance of a single diode photovoltaic module power output model.The formulated model results were validated with rated power output of a photovoltaic module provided by manufacturers using local meteorological data, which gave ±2% error. It was found that the proposed model is more practical in terms of precise estimations of photovoltaic module power output for any required location and number of variables used.